A successful term pregnancy with severe hypertriglyceridaemia and acute pancreatitis. Clinical management and review of the literature. (December 2019) - Perrone, Seila; Brunelli, Roberto; Perrone, Giuseppina; Zannini, Ilaria; Galoppi, Paola; Di Giacomo, Serafina; Morozzi, Claudia; Pisciotta, Livia; Stefanutti, Claudia
Abstract: Background and aims: Acute hyperlipidaemic pancreatitis (HP) may develop in pregnancy in patients with genetic predisposition. There are no accepted guidelines for the management of this rare but life-threatening condition in pregnancy. Plasma exchange (PEX) was suggested as a suitable option to treat HP in pregnancy; however, further evidence from case reports/case series are needed. Methods: Three PEX procedures (2000 ml of plasma replaced with 5% albumin) were performed in one week in a pregnant patient at 25 weeks of gestational age with severe HP. Triglyceride related genes (LPL, APOA5, APOE, GPIHBP1, GPD1, LMF1, CREB3L3) were screened by DNA sequencing. Medline and Embase databases were searched electronically in January 2018 using different combinations of the relevant medical subject headings for "pancreatitis in pregnancy" and "therapeutic apheresis". Results: Gene profiling assessed a combined heterozygous state for the variants pSer19Trp of the APOA5 gene and pCys130Arg of the APOE (allele E4) gene. PEX led to significant and progressive reduction of triglyceride plasma levels along with cholesterol and C-reactive protein. Meanwhile a fast improvement of pregnant clinical condition was observed. This allowed the delivery at term of a healthy newborn without gestational complications. An outcome hardly achievable in patients managed exclusively by a pharmacological approach. Conclusions: PEX led to a positive maternal outcome in absence of foetal and gestational complications in a case of severe HP in pregnancy. As clinical trials are lacking, case reports still represent the best way to reasonably implement clinical management of this rare but life-threatening disease.